Perception of Students as a Beginner Voter on General Election in Cianjur District - Hermawan, Iyep Candra; Mulyadi, M Budi; Septian, Ari (International Journal of Criminology and Sociology, 2022)
In this simultaneous election, legislative elections for the regions, provinces, and the center as well as the election of presidential pairs. There is an assumption that with the simultaneous implementation of legislative and executive elections (Candidates for President-Vice President), there appears to be an imbalance between the election of the Candidates for President-Vice President and the legislature so that the presidential election contest gets more attention than the legislative election. The public is quite enthusiastic about welcoming this election with a public participation rate of 81%, which is quite high when compared to previous elections. This study examines students’ perceptions of the survey results regarding perceptions of the implementation system and socialization of the 2019 simultaneous elections on April 17, 2019. This study uses quantitative methods using a questionnaire to students. For beginner voters who in this study were represented to Universitas Suryakancana students with a sample of level 1 and level 2 students of the Teaching and Education Faculty, Universitas Suryakancana, with random sampling in the Cianjur district and sufficiently representative. The conclusions of this article are: 1) The campaign as a media of socialization and political education is seen as influencing the choice of candidates for both the executive and legislative elections; 2) Social media, which is seen as the most dominant in influencing voters’ preferences for both the executive and legislative elections; 3) Beginner voters saw a necessity and felt enthusiastic about voting and were very decisive on the vote acquisition; 4) The response of first-time voters to choices for executive and legislative elections is based more on the character and authority of the prospective leaders; 5) The reaction of first-time voters to political parties in a democratic government system requires multiple parties.